An analysis of metaphor in economic news headlines in English = Nghiên cứu về biện pháp ẩn dụ trong tiêu đề báo kinh tế bắng Tiếng Anh - Phạm, Thu Hoài (2021)
Using the theoretical framework of Conceptual Metaphor Theory as initiated by Lakoff and Johnson (1980), this study carried out an investigation into the use of the conceptual metaphor used for the headlines of economic news articles in the hope of helping ESP learners cope with figurative expressions and also giving some hints for Vietnamese translators. The thesis was particularly dealt with the perceptions of the economy as human beings, a machine, a plant, and as a building. The data collection for the analysis has been drawn from the specific field of the business sections of three newspapers: The Economist, Financial Times and CNNMoney, the Business Week, whereas all examples originate from the period between 2007 and 2010. Compiling a small corpus of non-literal instantiations as different authors have done will assist to identify whether the contextual meaning of a word or a multiword unit of headline contrasts with its basic meaning and whether the contextual meaning can be understood by comparison with that basic meaning, and then to categorize, the different linguistic realizations of a headline in terms of their syntactic structure, metaphor foci and source domains.